Minimum Global Tax (Pillar Two) and Developing Country Interests: An Indonesian Assessment (Indonesian Tax Justice Review, 2024)
The OECD/G20 Pillar Two Global Minimum Tax seeks to curb profit shifting by multinational enterprises. This paper evaluates the implications of Pillar Two for Indonesia’s taxing rights and fiscal sovereignty. Using doctrinal and policy analysis, the study assesses whether the income inclusion rule and undertaxed payments rule benefit developing countries. The findings suggest that Pillar Two primarily advantages residence countries hosting multinational headquarters. The global contribution of this study lies in offering a Global South critique of minimum taxation. Indonesia’s experience provides timely insights into the distributive consequences of emerging global tax rules. The paper contributes to global tax justice literature by questioning whether minimum taxation reforms adequately address developing country interests.